Addressing Key Management Techniques at Improved and Non-Conventional Water Resources - Mohamed A. ElFetyany, Mohamed Sherif S. Tony (International Journal of Advanced Science and Technology, 2020)
Asworld population is increasing, total water demand is steadily increasing. This appears clearly in most arid and semi-arid regions. Egypt is one of the semi-arid areas where agriculture consumption exceeds 80% of available water, and the freshwater balance becomes negative. This means that Egypt is steadily depleting its resources since domestic and industrial waters are considered predominant to agriculture. Meanwhile, fixed water supply, increasing demand, water quality threats, and water delivery complexity could be captured as the main issues that best describe water problems in Egypt. Because water management in Egypt is facing such major problems and challenges, pioneer irrigation improvement projects and wastewater reuse pilot endeavours were conducted aiming atsaving of irrigation water, increase use efficiency, and develop new, non-conventional resources (like wastewater).Meanwhile, water sector management must consider a wide range of issues including: resources size and quality, economic conditions, investment availability, site features, as well as community and stakeholders. Therefore, for continual improvement, a good management technique should be adapted to enable;reasonable utility selection, appropriate design, and operation. The aim of this study is to provide rational management and assessment tools for water management and reasonable selection criteria of irrigation improvement priority areas, through applying proven techniques. Applying the "Primer Concepts", "Pareto", and "Six Sigma" algorithms enable earlier weighing of different scenarios, analysis of risks and subsidies, maximizing the benefits from resources and investments, and predicting impact on different domains and levels. This research paper also provides an overview of the recent researches and development for the integrated management of water resources. Key outcomes included examples for application of developing the "Primer Concepts" for organizing water management utilities. Also the "Lean-Six-Sigma" tools were successfully applied for an irrigation improvement example, through planning and designing stages. In this paper; two pilot areas were primary selected by using the "Process Capacity Analysis", while causal analysis of the irrigation problems used "Pareto" technique. These criteria enabled determination of area-priority for improvement, and selection of the improving technique regarding: need, effectiveness, cost, liability and accessibility. The multiple benefits from applying such techniques comprised endorsing application elsewhere to ensure effectiveness and feasibility.